Modalização: uma estratégia argumentativa - Matos, Fernanda Cristina Vieira de (2009)
This work is inserted in the line of Research Reading, Writing and Teaching of Portuguese Language and it has as object of study the modality as argumentative strategy. This study intends to evidence, through the analysis of four chronicles, the importance of modality for the argument of the author. The fact of we acting as teacher in elementary and high school justified the realization of this research, which specific purposes were thus defined: 1. to verify how the modality occurs in the chronicles of Carlos Heitor Cony, published at Folha de S. Paulo newspaper (page 2, section Opinion); 2. to reflect, with basis in the analysis, about the modality as argumentative strategy of the author. To accomplish the purposes established, this study is founded in theoretical principles of the Theory of Argument, proposed by Perelmam (2005, 1993), Olbrechts- Tyteca (2005) and Mosca (2004); from the Theory of Speech Acts, according to Austin (1990) and Searle (2002); from Textual Linguistic, at Koch s perspective (2006, 2004), Castilho A. e Castilho C. (1993) and Neves (1996, 2000); from Enunciation Theory, according to Kerbrat-Orecchioni (1980); and from Journalism Theory, in accordance with Beltrão (1980) and Melo (2003). The results obtained in the analysis of the chronicles evidenced that the modality is present in Cony s chronicles, through modal linguistic marks (verbs, adverbs, nouns and adjectives), which allow the author to position himself in relation to what he writes, compromising himself with his text, printing his evaluation and judgment about facts, guiding, through his credibility, the opinion of his reader. It was also evidenced that the type of reader presupposed by Cony at the analyzed chronicles is the intellectual one, and, besides that the chronicles can be classified as general and as satirical humorous. We considered that the work development allowed us to deepen our knowledge about the subject, as well as to rethink our pedagogical practice and, consequently, bring some contributions to the teaching of reading